Effects of addition of 2-fucosyllactose to infant formula on growth and specific pathways of utilization by Bifidobacterium in healthy term infants - Wallingford, John C.; Neve Myers, Pernille; Barber, Cynthia M. (Frontiers in Nutrition, 2022)
Oligosaccharides in human milk support health via intestinal microbiome. We studied effects of addition of 2-fucosyllactose (2ʹFL) to infant formula and examined effects on infant growth, occurrence of adverse events and infant microbiome, including expression of microbial genes that metabolize 2-fucosyllactose (2ʹFL). In double blinded-randomized study fashion infant formula +/- 2ʹFL or breast milk was fed to healthy term infants for 16 weeks. Fecal samples obtained at baseline and week 16 were analyzed for microbial populations, metagenomic species concept (MGS) and genetics of gut metabolic modules (GMMs). There were no effects of addition of 2ʹFL on growth or adverse events. There were no significant differences by feeding group in MGS richness or Shannon diversity at baseline but formula groups each had significantly greater richness (p < 0.05) and diversity (p < 0.05) after 16 weeks of feeding than the Breastfed group. Two glycosyl hydrolase (GH) families (GH42 and GH112) were significantly increased while two other GH families (GH20 and GH2) were significantly decreased in the Test formula group compared to the Control formula group; while modest, addition of 2ʹFL resulted in changes in microbiome in the direction of breastfed infants, consistent with internal metabolism of HMOs by Bifidobacterium.